A Rare Kind of Lymphoma in a Patient on Treatment With Two Different Biological Agents - Inesa ARSTIKYTE,; Irena BUTRIMIENE,; Agne PETRULIONIENE,; Algirdas VENALIS, (Archives of Rheumatology, 2015)
In this article, we present a rare case of cutaneous pseudolymphoma which developed after treatment with two biologics: infliximab and rituximab. Cutaneous pseudolymphoma should be considered in the differential diagnosis of B- or T-cell lymphoma, which may present not only with local lesions, but also systemic features like fever, weight loss, night sweating, fatigue, and tiredness. In our case, skin biopsy with immunohistochemistry confirmed diagnosis of cutaneous pseudolymphoma. Treatment with systemic corticosteroids was effective.